MODELLING OF VERTICAL SOIL COLLECTORS OF THERMAL PUMPS - Sydorchuk, Bogdan; Naumchuk, Oleksandr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The mathematic model of non-stationary process of heat distribution in soil collector is made. Convection heat transfer in the tube of collector and in depth soil temperature are taken into account. Algorithm of soil collector determination of approximating transmission function collector is created. The results and diagrams of transitional processes and dynamic description of the object are given.